Теория этической речи в трактате Аристотеля “Риторика” [Vitalij Valchenko: Ἠθικὸς λόγος in Aristotle’s Rhetoric] - Вальченко, В. В. (Hyperboreus, 2026)
The posthumously published paper by V. Valchenko (1940–2006?) surveys the elements of the ἠθικὸς λόγος in Aristotle’s Rhetorics. According to the author’s opinion it is the specific type of argumentation which borrows its topics from ethics and politics, but is built in accordance with the logic in the same way as the ἀποδεικτικὸς λόγος.